1995
DOI: 10.3171/jns.1995.83.5.0799
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of neurovascular compression in trigeminal neuralgia with magnetic resonance imaging

Abstract: Until recently, the inability to demonstrate neurovascular compression of the trigeminal nerve preoperatively resulted in surgery being offered only in cases of severe trigeminal neuralgia (TGN), frequently after a prolonged trial of medical treatment and following less invasive procedures, despite the fact that posterior fossa microvascular decompression gives long-term pain relief in 80% to 90% of cases. To assess whether vascular compression of the nerve could be demonstrated preoperatively, high definition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
6

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(76 citation statements)
references
References 33 publications
2
68
0
6
Order By: Relevance
“…In contrast, trigeminal neuralgia is characterized by intermittent periods of sharp, electricity-like, shooting pain that results primarily from compression of the trigeminal root entry zone by an arterial vessel (Meaney et al, 1995;Hamlyn, 1997). Indeed, surgical interventions in which the offending artery is physically separated from the trigeminal nerve are successful at relieving this type of pain (Meaney et al, 1995;Leandri et al, 1998). Given these observations, it is thought that TMD and trigeminal neuralgia result from peripheral events, i.e., nociceptor or nerve root.…”
Section: Neuropathic Pain and The Thalamusmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, trigeminal neuralgia is characterized by intermittent periods of sharp, electricity-like, shooting pain that results primarily from compression of the trigeminal root entry zone by an arterial vessel (Meaney et al, 1995;Hamlyn, 1997). Indeed, surgical interventions in which the offending artery is physically separated from the trigeminal nerve are successful at relieving this type of pain (Meaney et al, 1995;Leandri et al, 1998). Given these observations, it is thought that TMD and trigeminal neuralgia result from peripheral events, i.e., nociceptor or nerve root.…”
Section: Neuropathic Pain and The Thalamusmentioning
confidence: 99%
“…TMD are characterized by throbbing, tender, continuous pain and result from or are initiated by activation of nociceptors in the temporomandibular joint and/or muscles of mastication (Sarlani and Greenspan, 2005;Ro, 2008;Sessle et al, 2008;Manfredini and Nardini, 2010). In contrast, trigeminal neuralgia is characterized by intermittent periods of sharp, electricity-like, shooting pain that results primarily from compression of the trigeminal root entry zone by an arterial vessel (Meaney et al, 1995;Hamlyn, 1997). Indeed, surgical interventions in which the offending artery is physically separated from the trigeminal nerve are successful at relieving this type of pain (Meaney et al, 1995;Leandri et al, 1998).…”
Section: Neuropathic Pain and The Thalamusmentioning
confidence: 99%
“…1,2,21 Sindou et al 21 quantified the degree of compression at surgery from Grade I to Grade III and showed that MVD offers a 15-year success rate of 88.1% if the NVC was Grade III, 78.3% if the NVC was Grade II, and only 58.3% if the NVC was Grade I. Meaney et al 19 reported MRI findings of nerve grooving in 13 and distortion or deviation of the nerve in 16 of 50 symptomatic individuals; these 29 patients had the most favorable outcomes after MVD. Our data could provide guidance for choosing the best surgical option, which must be based not merely on the surgeon's preference, but on objective anatomical and pathological evidence.…”
Section: Correlation Among Tgn Atrophy Patient Characteristics Nvc mentioning
confidence: 99%
“…At operation, Tew et al [60] found a "significant" impingement in less than half of 50 patients in whom preoperative study showed arterial loop and neurovascular contact. Fortunately, today magnetic resonance imaging (MRI) is a reliable technique to study neurovascular interaction at the trigeminal root entry zone [64,[77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] and it must be performed in every TN patient candidate to MVD. Meaney et al [86], sustaining that MRI is "an extremely sensitive and specific method for demonstrating vascular compression in TN", concluded that "open surgical procedures can be recommended with confidence".…”
Section: Selection Of Patientsmentioning
confidence: 99%